Cover Picture: Elucidation of the Sodium – Copper Extrusion Mechanism in CuCrS2: A High Capacity, Long‐Life Anode Material for Sodium‐Ion Batteries (Batteries & Supercaps 5/2018). Issue 5 (24th September 2018) - Krengel, Markus; Hansen, Anna‐Lena; Hartmann, Felix; van Dinter, Jonas; Bensch, Wolfgang
Abstract : The front cover artwork is provided by the group of Prof. Bensch at the inorganic chemistry department of Christian‐Albrechts‐University Kiel (Germany). The image illustrates the copper – sodium extrusion mechanism in CuCrS2 during the first step of sodium uptake. Additionally, the results of ex‐situ X‐ray diffraction measurements and pair distribution function measurements are displayed.More information can be found in the article by M. Krengel et al. (DOI:10.1002/batt.201800039 ).